Technology fetishism in The Wandering Earth. - Khan, Amir (Inter-Asia Cultural Studies, 2020)
My claim is that Frant Gwo's film, The Wandering Earth (2019), fetishises technology and, in so doing, forces Western audiences of the film to face an otherwise outdated thematic motif of social togetherness or solidarity. That is, the exquisite onscreen rendering of advanced technological achievement (the construction of 10,000 Earth Engines designed to drive the planet to inhabit another solar system after the sun begins to rapidly deteriorate) acts as an aesthetic Trojan Horse. We in the West are seduced by the slick technological hardware showcased in the film; from there, however, the film forces us to ask if such advanced technology can be achieved outside of the profit-motive. The capable visual rendering of technological progress subtly masks a more subversive political message critiquing Western colonization of the planet. In the end, the film asserts China's right to lead humanity past impending global disaster not simply (nor solely) by making the necessary hard technological leaps, but by mobilizing the necessary collective energy and will of the world's colonized and oppressed.